2019
DOI: 10.20868/bma.2019.2.3924
|View full text |Cite
|
Sign up to set email alerts
|

An improvement in construction planning: Last Planner System ® = Una mejora en la planificación de la construcción: el sistema del último planificador

Abstract: For approximately five years, the Last Planner System ® has been used more and more in Spain, due to the improvement that its use produces in the productivity of the construction, reaching, with its use, better results in the achievement of the objectives of: Cost, time and quality of the projects. But still it is necessary its knowledge and diffusion so the application of this System will be normal in all our works. It was Professors Glenn Ballard and Greg Howell of the University of Berkeley in California, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Previous studies have analysed and confirmed the causal link between workflow variability reductions and project performance improvements (Howell et al. , 2004; Choy and Ruwanpura, 2006; Pérez et al. , 2019).…”
Section: Data Collectionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have analysed and confirmed the causal link between workflow variability reductions and project performance improvements (Howell et al. , 2004; Choy and Ruwanpura, 2006; Pérez et al. , 2019).…”
Section: Data Collectionmentioning
confidence: 80%
“…Therefore, LPS was developed to shield downstream operations from upstream variability (Ballard and Howell, 1994) and the Last Planner tool is advised to be compared to and complemented by, to a certain degree, measuring productivity (Choy and Ruwanpura, 2006; González et al. , 2008, 2010; Pérez et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…is format shows what will be done in the coming four to six months. And it helps to forecast the resources needed for each activity (5) Weekly work plan: at this stage, constraint-free tasks are made ready for the coming week. Apply quality criteria (definition, size, sequence, soundness, and learning).…”
Section: Conceptual Framework Discussionmentioning
confidence: 99%
“…e Last Planner system owes its origin to the studies by Professors Glenn Ballard and Greg Howell of the University of California at Berkeley, United States, in the 90s, and their knowledge of Professor Lauri Koskela, of the University of Helsinki, Finland. ese works were formalized in scientific articles within the Lean Construction Institute, which they founded together [5].…”
Section: Last Planner Systemmentioning
confidence: 99%